Effects of Recycling on the Mechanical Behavior of Polypropylene at Room Temperature Through Statistical Analysis Method. Issue 11 (1st June 2016) - Khademi, Fatemeh; Ma, Yongsheng; Ayranci, Cagri; Choi, Keith; Duke, Kajsa
Abstract : This article reports the effects of recycled material percentage, annealing conditions, and glass fiber percentage on the mechanical behavior of injection molded polypropylene samples. Specimens were prepared with different percentages of recycled material ranging from 0 to 100%. Two groups of samples, i.e., non‐annealed and annealed at 150°C, were tested to investigate annealing effects. The effects of adding fiber (0–7.5%) to specimens was also investigated. It was found that increasing the amount of recycled material improves the material properties in a non‐linear trend. Annealing had a significant positive effect on both non‐fiber‐added and fiber‐added samples: it improved the yield stress of non‐reinforced polypropylene samples by more than 10% and their Young's modulus by about 50%. Fiber‐added materials showed more variability, and adding fiber also improved the Young's modulus and the yield stress of the samples by about 50%. The results indicate that the three factors investigated improved toughness of the injected polypropylene samples; however the effects are not significant. The study findings reveal that using recycled polypropylene has no significant effect on the material properties of polypropylene. POLYM. ENG. SCI., 56:1283–1290, 2016 © 2016 Society of Plastics Engineers